1987
DOI: 10.1161/01.res.61.5.757
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of free radicals in the reperfused rat heart using electron spin resonance spectroscopy.

Abstract: The purpose of this study was to use a direct method, that of electron spin resonance (ESR) spectroscopy, to demonstrate that reperfusion after a period of ischemia results in a sudden increase in the production of free radicals in the myocardium. The isolated buffer-perfused rat heart was used with N-tert-butyl-alpha-phenylnitrone (PBN) as a spin-trapping agent. Samples of coronary effluent were taken and extracted into toluene for detection of radical adducts by ESR spectroscopy. After 15 minutes of total, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
197
0
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 581 publications
(211 citation statements)
references
References 20 publications
13
197
0
1
Order By: Relevance
“…Reperfusion of an ischaemic tissue can be accompanied by the release of redox-active transition-metal ions [230] and a burst of radicals [231] whose formation requires O # . In working rat hearts, reperfusion is accompanied by a large rise in protein carbonyls within 5 min, followed by a return within 15 min almost to basal levels [232].…”
Section: Oxidized Proteins and Toxicity To The Host Organismmentioning
confidence: 99%
“…Reperfusion of an ischaemic tissue can be accompanied by the release of redox-active transition-metal ions [230] and a burst of radicals [231] whose formation requires O # . In working rat hearts, reperfusion is accompanied by a large rise in protein carbonyls within 5 min, followed by a return within 15 min almost to basal levels [232].…”
Section: Oxidized Proteins and Toxicity To The Host Organismmentioning
confidence: 99%
“…Recent evidence suggests that postischaemic myocardial dysfunction (stunning) may represent a functional or nonlethal form of reperfusion injury (Braunwald & Kloner, 1982;Kloner et al, 1989) and oxygen free radicals may contribute to the pathogenesis of myocardial stunning (Gross et al, 1986;Bolli et al, 1987;1989;Forman et al, 1988;Faber et al, 1988). Bolli and his colleagues (1988) using electron paramagnetic resonance spectroscopy detected a burst of free radical formation within the coronary venous effluent in dogs subjected to 15min of coronary occlusion and reperfusion; other studies found that production of free radicals increased markedly in isolated hearts of rabbit or rat undergoing global ischaemia and reperfusion (Zweier et al, 1987;Garlick et al, 1987; Kramer et al, 1987) and pretreatment with the oxygen radical-scavenging agents superoxide dismutase and catalase reduced the degree of left ventricular dysfunction in canine models of stunned myocardium (Gross et al, 1986;Ambrosio et al, 1987;. Nevertheless, recent studies also indicate that other factors independent of free radicals are involved in the pathogenesis of myocardial stunning such as: calcium overload (Kusuoka et al, 1987; Lee et al, 1987;Steenbergen et al, 1990;Sun & Lin, 1990), heterogeneous impairment of myocardial perfusion (Stahl et al, 1986) and neutrophil accumulation in the postischaemic myocardium (Westlin & Mullane, 1989) and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the ESR signals thus recorded are potentially free from possible artifacts arising from fast free~ing, cold storage and thawing processes. Moreover, spectra acquired during pre-ischemic control perfusion with the nitrone-supplemented chelexed buffer never exhibit any detectable signal while control spectra published by previous investigators [23,24,26,27,47] generally showed little, but yet visible, spin-adduct formation uncorrelatcd to the ischcmicinduced biological free-radical production.…”
Section: Lipid Extracts Discussionmentioning
confidence: 76%
“…The most commonly used free-radical scavengcr has been MezPnO either on rabbit [26] or on rat hearts [23 -251. A limited number of experiments was based on BuPhNO on rat [27] or dog [28] hearts. In all cases, collected samples of coronary effluents were promptly freezed and subsequently thawed for ESR analysis.…”
Section: Lipid Extracts Discussionmentioning
confidence: 99%